Effect of potassium sorbate and calcium propionate on the storage period of stuffed pastry (Pork Lard and Butter) - Apelit, Margie B. (1997.)
The effectivity of potassium sorbate and calcium propionate to extend the storage period of hopia baboy and butter was studied.
Thesis - B.S. (Food Technology) - SOTECH, University of the Philippines in the Visayas.
Keywords: Potassium Sorbate; Calcium propionate; Stuffed Pastry